2021
DOI: 10.1111/dme.14577
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 Epidemic on hospitalization for diabetic foot ulcers during lockdown: A French nationwide population‐based study

Abstract: Aims/hypothesis: The aim of this study was to examine the impact of the COVID-19 epidemic on the hospitalization rates for diabetic foot ulcer (DFU), osteomyelitis and lower limb revascularization procedure in people with DFU. Methods: This nationwide retrospective cohort study included hospital data on all people hospitalized in France for diabetes in weeks 2-43 in 2020, including the COVID-19 lockdown period, compared to same period in 2019. Results: The number of hospitalizations for DFU decreased significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 11 publications
3
31
1
Order By: Relevance
“…Lipscomb et al, 24 working within a regional ambulatory diabetes care program in the United Kingdom, reported fewer DFU events observed during their Spring 2020 lockdown. Mariet and colleagues 11 reported fewer DFUs and fewer amputations during the 2020 lockdown across France. Valabhji et al 12 also advanced this hypothesis in their report showing fewer amputations among people with diabetes in England.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipscomb et al, 24 working within a regional ambulatory diabetes care program in the United Kingdom, reported fewer DFU events observed during their Spring 2020 lockdown. Mariet and colleagues 11 reported fewer DFUs and fewer amputations during the 2020 lockdown across France. Valabhji et al 12 also advanced this hypothesis in their report showing fewer amputations among people with diabetes in England.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 2 recent population-based studies of people with diabetes in England and France identified a decrease in limb loss during the pandemic, potentially explained by limited daily activities during lockdown translating to fewer neuropathic foot ulcers. 11 , 12 However, these analyses did not capture the comorbidity profile of individuals undergoing amputation during the pandemic relative to historical controls to explore the possibility of excess mortality precluding amputation during the pandemic. Furthermore, diabetes care measures (eg, foot examination and hemoglobin A 1c [HbA 1c ] measurement) associated with short- and long-term amputation risk were not studied.…”
Section: Introductionmentioning
confidence: 99%
“…On study from Italy, reported a threefold higher amputation rate in 2020 compared to the year 2019 ( Caruso et al, 2020 ) and another from China also reported significant disruption of routine foot care provision ( Liu et al, 2020 ). One study reported that there was a precipitous decrease in hospitalisation rates for diabetic foot ulcers during the first French lockdown and fewer revascularisations were undertaken ( Mariet et al, 2021 ). Monitoring for diabetic kidney disease has also been reported to decline during the pandemic due to redirection of scare healthcare resources ( Gregg et al, 2021 ).…”
Section: Diabetes and Covid-19 Outcomesmentioning
confidence: 99%
“…8 Overall, the existing evidence suggests that restricted access to healthcare during the pandemic increased the risk of DFO development and related adverse outcomes. 4 Nevertheless, the available data represented only one European country, leaving space only for assumptions regarding other countries and continents. The potential of telemedicine was highlighted.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Following the lift of the restrictions, DFO rates were rapidly increased reaching the pre‐pandemic levels and in some cases surpassing them. 4 .…”
mentioning
confidence: 99%